Kekuatan Bahan Tali Tampar - Edi Hari Purwono; Bambang Yatnawijaya (RUAS (Review of Urbanism and Architectural Studies), 2013)
One of the construction systems and structures to be learned by a designer or architect is the construction and long-span structures. Application of long-span structures using cable as the main buffer in Indonesia is considered late whereas in some developed countries have been well developed. The main factors which may be considered the cause of this case is the lack of material knowledge which is synthetic rope. Synthetic rope is considered as capable as steel cable on a small scale. This research is conducted for public and academics to know how far is the strength of synthetic rope for modeling compared to steel cable. The method used is an experimental method of empirical testing by the test material on the tools that have been provided. Additionally, content analysis method in literature source and previous research is also used to get the data needed. Experiments conducted did not show the detailed measurement accuracy but with a certain value limit that can be seen by the eyes and senses.Keywords: Strength of materials, synthetic rope